(untitled) (Reflection and Critique Law Magazine, 2022)
The present study aims at the synthetic and systematic analysis of the normative dispositions of the Consumer Protection Code (CDC), in terms of individual rights, as a well-known landmark in the recognition of collective demands, as well as future reflections. The approach remains from the new form of social organization, the consumption of products and services, elementary to the subsistence of the population. This reality causes the State to infer in consumer relations, in order to ensure the equality between those involved. In Brazil, the Constitution of the Federative Republic of Brazil (CRFB) of 1988 and the CDC in 1990 established a beneficial scenario for consumers, marking the balance of the relationship with the suppliers, strengthening the social vision by the legislator to consumer relations, encompassing a larger contingent of individuals in the measure of their interests and relations of fact, inaugurating a new legal approach on collective rights.